Investigating the Impact of Green Marketing on Stay Decisions: The Mediating Role of Green Consumer Behavior - Ni Made Ayu Natih Widhiarini; Theresia Pradiani; Fathorrahman (Universitas Pendidikan Ganesha, 2023)
Changes in the behavior of tourists after the COVID-19 pandemic, who are more concerned with sustainable impacts, have intensified the implementation of green marketing, including the emergence of various environmentally friendly accommodations such as glamping. However, almost no research that examines the application of green marketing in glamping accommodation, especially in Indonesia. The purpose of this study is to investigate the application of green marketing in glamping accommodation, especially in Indonesia, given the lack of research that has been conducted in this context. This research type used quantitative methods. Data collection was conducted by distributing a questionnaire in google form to 100 tourists who stayed at Pelaga Eco Park Glamping, Bali, Bali between August – September 2022. The sample was taken using an accidental sampling technique. The analytical method used is Path Analysis using SEM-PLS. The results showed green marketing has a positive and significant effect on the decision to stay; green marketing has a positive and significant impact on green consumer behavior; green consumer behavior has a positive and significant impact on the decision to stay; green consumer behavior can be an intervening variable partially on the influence of Green marketing with the decision to stay. This research implies that glamping managers can be more concerned about planning and implementing green marketing to win the market while contributing to environmental sustainability.